Victims in the Criminal Process: A Utilitarian Analysis of Victim Participation in the Charging Decision - Welling, Sarah N. (1988)
Crime victims are currently being given the right to participate in criminal prosecutions at both the sentencing and plea bargaining stages. These are important steps in a criminal prosecution, but both the sentence and the plea bargain are dependent on the initial charging decision which determines what crime is to be prosecuted or whether there is to be any prosecution at all. As a prerequisite to both a plea bargain or a sentence, the charging decision is the crux of the prosecution. Given the importance of the charging decision, and the fact that some jurisdictions have granted victims a right to participate in plea bargains and sentencing, should victims also have a right to participate in the charging decision? Although providing information to victims about the charging decision has been endorsed, there is resistance to victim participation in the decision. This resistance to victim participation is implicit, without explanation. While the resistance to the idea of victim participation may simply be the product of a conservative bias against change, it is more likely born of suspicion that the concern for victims' rights is a pretext to limit defendants' rights and implement prosecution oriented changes in the system. This Article examines whether victims should be accorded a right to participate formally in the charging decision. The perspective is primarily utilitarian, the premise being that if victim participation is, on balance, useful, there is no reason to reject it. The Article begins by assessing the costs and benefits of victim participation in the charging decision. The first section analyzes the parties' interests in the charging decision, and the impact establishing a victim's participation right has on those interests. The second section examines the current role of victims in the charging decision. The third section analyzes the source of the charging decision, the prosecutor, and limits on the prosecutor's discretion. The fourth section defines a method of according victims a right to participate in the charging decision. The Article concludes that victim participation in the charging decision can be useful if the right to participate in the decision-making process is carefully designed